1995
DOI: 10.1111/j.1399-0039.1995.tb02460.x
|View full text |Cite
|
Sign up to set email alerts
|

Early‐onset pauciarticular juvenile chronic arthritis is associated with a mutation in the Y‐box of the HLA‐DQA1 promoter

Abstract: Early-onset pauciarticular juvenile chronic arthritis (EOPA-JCA) has associations with different alleles of the MHC region (HLA-A2, DR5, 6, 8, DQA1*0401, *0501, *0601 and DPB1*0201). All susceptible DQA1 alleles carry an exclusive sequence motif. MHC-class II gene expression is controlled by 5' flanking upstream regulatory regions (URR). A hypervariable region in the promoter region of the HLA-DQA1 gene (-240 and -200 base pairs upstream) defines ten different QAP (DQA1-Promoter) alleles, which are associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 22 publications
1
26
0
5
Order By: Relevance
“…Position ±238 corresponds to a nucleotide site particularly conserved among TNFA Y boxes of different species and among different MHC class II genes [23]. In the mouse the TNFA promoter Y box binds an abundant nuclear factor and is involved in the baseline expression of the TNFA gene [24], while a single base pair substitution in the Y box of the HLA-DQA1 promoter has recently been shown to significantly decrease transcription [25]. Studies aimed at obtaining direct evidence for the effect of the ±238 polymorphism on TNFa expression are currently ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Position ±238 corresponds to a nucleotide site particularly conserved among TNFA Y boxes of different species and among different MHC class II genes [23]. In the mouse the TNFA promoter Y box binds an abundant nuclear factor and is involved in the baseline expression of the TNFA gene [24], while a single base pair substitution in the Y box of the HLA-DQA1 promoter has recently been shown to significantly decrease transcription [25]. Studies aimed at obtaining direct evidence for the effect of the ±238 polymorphism on TNFa expression are currently ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of the NF-YA DNA binding protein as it relates to HLA-DR expression appears to be unique to our system. Others have reported that the absence of NF-YA increases HLA-DR expression and increases the susceptibility to rheumatoid arthritis (20,64). Interestingly, the NF-YA protein binds to the long terminal repeat of HIV-1 and human T-cell leukemia virus type 1, can activate transcription of viral gene products, and is related to Rous sarcoma virus enhancer factor I (13,26,63).…”
Section: Hiv-1 Affects Hla-dr Transcriptionmentioning
confidence: 99%
“…Furthermore, DQA1 promoter region polymorphisms are associated with quantitative expression differences in cell lines (14), and they affect the strength of transcription factor binding (15). Moreover, specific human DQA1 proximal promoter alleles may be associated with increased susceptibility to a number of autoimmune and infectious diseases (16)(17)(18).…”
mentioning
confidence: 99%